Bùi Hồng Thắm
8 tháng 11 2015 lúc 20:11

\(2+3.\left(\frac{-1}{3}\right)^2\)

=\(2+3.\frac{1}{9}\)

\(2+\frac{1}{3}\)

=\(\frac{7}{3}\)

Bình luận (0)
Nguyễn Ngọc Quý
8 tháng 11 2015 lúc 20:09

= (-1/3.3).(-1/3) + 2 = 1/3 + 2 = 7/3        

Bình luận (0)

Các câu hỏi tương tự
Pham Trong Bach

Tính giá trị biểu thức một cách hợp lí

1) B = 5 − 3 4 + 1 5 − 6 + 7 4 − 8 5 − 2 − 5 4 + 16 5

2)  C = − 2 3 + 1 − 7 5 − 0 , 2 + 7 15 − 1 + 4 3

3)  D = − 0 , 25 − − 3 4 − − 7 3 + − 9 2 − 5 6

4) E = 1 − 2 5 − 4 3 − 0 , 8 − 1 − 1 , 4 + 2

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN